1983
DOI: 10.2170/jjphysiol.33.869
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Cl- activity of canine submandibular gland cells: An in vitro observation.

Abstract: Summary Intracellular C1 activity (act) and transmembrane potential (d Y' m) of canine submandibular gland cells were measured in vitro by using Cl-sensitive liquid membrane microelectrodes. Under the conditions of superfusion with a control solution, average Cl-activity of the resting cells was slightly higher than those predicted from Nernstian equilibrium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…In the following, we give specific figures for the concentrations in the basolateral extracellular space ([Na]1, [K]1, [Cl]1), in the intracellular compartment ([Na]i, [K]i, [Cl]i), and in the lumen ([Na]2, [K]2, [Cl]2), and for their respective potentials, V1, Vi and V2 which are consistent with available information (e.g. Poulsen & Oakley, 1979;Mori, Murakami, Nakahari & Imai, 1983;Sasaki et al 1983) and which yield fluxes in the directions shown in the Figure. For simplicity, only Na, K and Cl are considered.…”
Section: Ca-dependent Channels In Lacrimal Glandssupporting
confidence: 84%
“…In the following, we give specific figures for the concentrations in the basolateral extracellular space ([Na]1, [K]1, [Cl]1), in the intracellular compartment ([Na]i, [K]i, [Cl]i), and in the lumen ([Na]2, [K]2, [Cl]2), and for their respective potentials, V1, Vi and V2 which are consistent with available information (e.g. Poulsen & Oakley, 1979;Mori, Murakami, Nakahari & Imai, 1983;Sasaki et al 1983) and which yield fluxes in the directions shown in the Figure. For simplicity, only Na, K and Cl are considered.…”
Section: Ca-dependent Channels In Lacrimal Glandssupporting
confidence: 84%
“…The evidence includes the demonstration that secretion can be blocked by furosemide (Case et al, 1982(Case et al, , 1984Martinez and Cassity, 1985a;Novak et al, 1984;Novak and Young, 1986;, and by removal of extracellular C1 (Case et al, 1984;Lundberg, 1958;Murakami et al, 1986;Novak and Young, 1986;Martinez and Cassity, 1985b). Additional evidence includes the demonstration that the secretary system shows a marked preference for Br and Cl over other anions (Case et al, 1982(Case et al, , 1984Novak and Young, 1986), a preference that is characteristic of Na-K-2C1 symports (Ellory et al, 1982), that cytosolic Cl activity is above equilibrium both at rest and during stimulation (Lau and Case, 1986;Martinez and Cassity, 1985a;Mori et al, 1983;Poulsen and Kristensen, 1982), and that six C1 ions are transported per ATP molecule, indicative of a process coupling C1 and Na fluxes in a ratio of 2:1 (Smaje et al, 1986). In salivary glands, however, there is good evidence to show that secretion can persist, albeit at a reduced rate, even when symport activity has been halted, and it is thought that this residual secretion is due to the operation of a Na-H antiport, which concentrates HCO3 in the cytosol, and a Cl-HCO3 antiport, which allows the cytosolic HCO3 to exchange for interstitial C1 (Case et al, 1982(Case et al, , 1984Martinez and Cassity, 1985c;Novak and Young, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…5A and B). The time between the break-in artifact and the peak of the transient ranged from 0-8 to 2-0 s, and the transient amplitude varied from 100 to 600 pA. Acinar cells from exocrine glands have a rather large internal Cl-concentration (Mori, Murakami, Nakahari & Imai, 1983;Saito, Ozawa, Hayashi & Nishiyama, 1985) such that at -60 mV, a substantial (approximately 25 mV) driving force exists for Cl-exit. (For the short times considered here ionic exchange between pipette and cell compartments may be neglected.)…”
mentioning
confidence: 99%